If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2e + -12 = 7e + 20 Reorder the terms: -12 + 2e = 7e + 20 Reorder the terms: -12 + 2e = 20 + 7e Solving -12 + 2e = 20 + 7e Solving for variable 'e'. Move all terms containing e to the left, all other terms to the right. Add '-7e' to each side of the equation. -12 + 2e + -7e = 20 + 7e + -7e Combine like terms: 2e + -7e = -5e -12 + -5e = 20 + 7e + -7e Combine like terms: 7e + -7e = 0 -12 + -5e = 20 + 0 -12 + -5e = 20 Add '12' to each side of the equation. -12 + 12 + -5e = 20 + 12 Combine like terms: -12 + 12 = 0 0 + -5e = 20 + 12 -5e = 20 + 12 Combine like terms: 20 + 12 = 32 -5e = 32 Divide each side by '-5'. e = -6.4 Simplifying e = -6.4
| f(x)=0.045(x-5)+100 | | 3/4w=-24 | | 12*x=0.4 | | x-.20=320 | | .10(38-x)=38(.08) | | 4+m=-1.12 | | 4(3+x)=144 | | 3a-13= | | 6+b=1-2n+5 | | T^2+10z+22=0 | | 98x-4=21x+3 | | x^2-10x+1296=0 | | -11=b-5 | | 63x^20y^16/3x^9y^15= | | -2/c-4=3 | | 3[x-2(x+1)]=3x+12 | | x^22-5x-6=0 | | 3m+2(m+5)-6=0 | | x+.10(38-x)=38(.08) | | -a+4(a+3)=-12 | | -z^2-4z+2=0 | | 11=6+h | | 2x-10=5x+50 | | 9(3m+8x-5n)= | | 2(c+5)=8 | | C=25x+550 | | .75w=-24 | | 3x-4=x-12 | | -6(k-7)-2(-4k+6)=7k+5k | | 5y=0-15 | | 3(4x-1)(4x+3)=48x | | 4.2+m=8.3 |